2004
DOI: 10.1002/bit.20098
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular enzyme loss during polyelectrolyte flocculation of cells from fermentation broth

Abstract: Association of extracellular protein product with flocculated cells reduces product yield. Here, partitioning of the enzyme subtilisin between the liquid and polyelectrolyte-flocculated and sedimented Bacillus increased as the polymer dosage was increased beyond that necessary to obtain optimum floc character (brain floc) for cell removal by centrifugation. Partitioning to the cell floc is partly physical entrapment at all polymer dosages; however, at higher levels there is also direct interaction between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The reduction of impurities by flocculation and centrifugation can enhance further downstream processes (Balasundaram et al, 2009;Singh et al, 2016;Felo et al, 2015). However, Pearson et al, observed enzyme losses during polyelectrolyte flocculation and explained possible reasons for these losses (Pearson et al, 2004b). According to their study, the product can either interact with the flocculant or be entrapped in the flocs, leading to changes in product yield.…”
Section: Evaluation and Scale-up Of Flocculation And Centrifugationmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of impurities by flocculation and centrifugation can enhance further downstream processes (Balasundaram et al, 2009;Singh et al, 2016;Felo et al, 2015). However, Pearson et al, observed enzyme losses during polyelectrolyte flocculation and explained possible reasons for these losses (Pearson et al, 2004b). According to their study, the product can either interact with the flocculant or be entrapped in the flocs, leading to changes in product yield.…”
Section: Evaluation and Scale-up Of Flocculation And Centrifugationmentioning
confidence: 99%
“…As already concluded from the sequential analysis, the feed variability influenced flocculation and centrifugation performance. Pearson et al, already identified batch variability as the most important factor for enzyme loss variability (Pearson et al, 2004b). Barany & Szepesszentgyörgyi detected an influence of suspension concentration and composition on flocculation efficiency, showing that suspension characteristics and content may vary from batch-to-batch (Barany and Szepesszentgyörgyi, 2004).…”
Section: Use Of Pca and Pls For Factor-screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Batch to batch variability in the fermentation broth was controlled by using broth from the same fermentation for all of the experiments where direct comparisons were made; however, several batches of fermentation broth were used with similar results obtained for different broths at the same experimental conditions. The engineered subtilisin has a molecular weight of 28 kDa and a pI of 6.8 giving it a positive charge at the filtration pH of 6.5 [38]. Table 1 gives the characteristics of the cationic polyelectrolytes used for these experiments (Kemira Water Solutions, Lakeland, FL).…”
Section: Feed Preparationmentioning
confidence: 99%
“…Classical filtration with a bacterium such as E. coli is constrained by cell size. Flocculating agents have been applied but tend to interfere with the product (52). Some lysis of E. coli harvested by disk centrifuges has been observed (53, 54).…”
Section: Cell Harvestingmentioning
confidence: 99%